Deciphering vancomycin resistance in Enterococcus faecium: gene distribution, sequence typing, and global phylogenetic analysis - Yan, Ruyu; Ji, Jun; Shen, Han; Cao, Xiaoli (Frontiers in Microbiology, 2025)
ObjectiveThis study analyzes the global prevalence and distribution of vancomycin resistance genes (van) in Enterococcus faecium and examines the genetic relationship and epidemiological characteristics of strains carrying these genes.MethodA total of 3,256 E. faecium genome sequences were downloaded, and 2,235 high-quality genomes were retained after quality filtering. The blastn tool was used to screen these genomes for van genes, and sequence types (STs) were determined using pubMLST profiles.ResultAmong the 2,235 genomes, 1,071 (47.9%) harbored van genes, with eight genotypes identified, including vanA, vanB, vanD, and vanM, accounting for 47.6%. There were 83 distinct STs among the strains carrying van genes, with ST17 being the most prevalent. Most strains carrying van genes were isolated from humans, primarily in the United States, and commonly from rectal swabs. In 2015, vanA was the most prevalent van gene, particularly in ST17 strains.ConclusionThis study highlights the widespread distribution of van genes and their significant presence in human populations and clinical settings, emphasizing the importance of monitoring and intervening in the spread of ST17 strains.